Application of pyridine-modified chitosan derivative for simultaneous adsorption of Cu(II) and oxyanions of Cr(VI) from aqueous solution. (15th March 2021) - Jorge Gonçalves, Fernanda; Alves Gurgel, Leandro Vinícius; Catone Soares, Liliane; Simões Teodoro, Filipe; Dias Ferreira, Guilherme Max; Coelho, Yara Luiza; Mendes da Silva, Luis Henrique; Prim, Damien; Gil, Laurent Frédéric
Abstract: The bioadsorbent C1, which is a chitosan derivative prepared in a one-step synthesis, was successfully used to adsorb Cr(VI) and Cu(II) simultaneously. Here, for the first time the simultaneous adsorption of a cation and an anion was modeled using the Corsel model for kinetics and the Real Adsorbed Solution Theory model for equilibrium data. Batch studies of the adsorption of Cu(II) and Cr(VI) in single and binary aqueous solutions were performed as a function of initial solute concentration, contact time, and solution pH. The maximum adsorption capacities of C1 in single and binary aqueous solutions were 1.84 and 1.13 mmol g −1 for Cu(II) and 3.86 and 0.98 mmol g −1 for Cr(VI), respectively. The reuse of C1 was investigated, with Cu(II) ions being almost completely desorbed and fully re-adsorbed. For Cr(VI), the desorption was incomplete resulting in a lower re-adsorption. Energy-dispersive X-ray spectroscopy was used for mapping the distributions of Cr(VI) and Cu(II) adsorbed on the C1 surface in single and binary adsorption systems. Isothermal titration calorimetry experiments were performed for Cr(VI) and Cu(II) adsorption in single solutions. The thermodynamic parameters of adsorption showed that the adsorption of both metal ions was enthalpically driven, but entropically unfavorable. Graphical abstract: Image 1 Highlights: A biosorbent (C1 ) from chitosan was synthetized using a one-pot reaction method. C1 efficiently removed Cu(II) and Cr(VI) from single and binary aqueous solutions. Corsel and Real Adsorbed Solution Theory models were employed for binary adsorption. Adsorption, desorption, and re-adsorption of the ions were performed in batch mode. The maximum adsorption capacities of Cu(II) and Cr(VI) were 0.98 and 3.86 mmol g −1 .